(untitled) (Journal of Comparative Social Work, 2022)
Our study focused on identifying the ethical challenges employees of gerontological social work have faced during Covid-19 pandemic. The ethical guidelines, based on international ethical principles of social work (IFSW), play a key part in Finnish social work. Still, even in normal times social workers face situations in which they are forced to work against professional ethical principles. Covid-19 pandemic changed the working conditions of social work dramatically and employees of gerontological social work have been in the front line working with elderly, who are vulnerable to the virus but also to the social repercussions of the pandemic. This qualitative interview study, based on 14 semi-structured interviews of employees of gerontological social work from different parts of Finland, was conducted between November 2020 and February 2021. Data was analyzed by using qualitative content analysis. The results showed that the employees’ biggest ethical challenge was related to the shutting down of elderly people’s services and the reduced possibilities to meet their clients. The participants described feeling helpless because they could not respond to their clients’ needs. Also, the unclear instructions given on how to respond to the threat of Covid-19 were making ethical practices difficult. In addition, the participants were worried about the increased loneliness and depression of their clients and were anxious on how to respond to the growing service needs of elderly with very limited resources. As times were rough, the participants would have needed of their colleagues’ support, which they now lacked because of remote working. They also described the lack of acknowledgement by their employers.